Identifying potential threats to economic security in a commercial organization - O. A. Ageeva; Yu. D. Matytsyna (Вестник университета, 2023)
The article reveals methods of identifying potential threats to economic security of commercial organization, primarily the algorithm of express diagnostics of its financial and economic activities. The purpose of the study is to identify threats to economic security of commercial organization and to build an algorithm to eliminate them with the help of internal control tools. The objectives are to conduct a financial analysis of organization, to systematize main indicators subject to evaluation, to identify the most significant threats and, as a consequence, to develop measures to strengthen economic security of commercial organization. The methodology of the research consisted in generalizing existing internal control toolkit, as well as in developing recommendations to improve economic security of commercial organization. The internal control methodology developed by the authors and presented in the article to identify and eliminate threats to economic security of commercial organization differs from existing similar methods in that it supplements internal threats with a new specific type of threats, on the one hand, arising externally, and on the other hand – affecting commercial organization directly at the micro level. It has been proposed to eliminate such threats with the help of the internal control system by expanding its tools.